TRACE METAL SIGNATURES OF JURASSIC/CRETACEOUS BLACK SHALES FROM THE NORWEGIAN SHELF AND THE BARENTS SEA - Lipinski M.; Warning B.; Brumsack H.J. (My University, 2003)
Black shale samples of Jurassic to Cretaceous age recovered during the 'Norwegian Shelf Drilling Program' between 1987 and 1991 from Sites 7430/10-U-01 (Barents Sea), 6814/04-U-02 (Norwegian Shelf near the Lofoten) and 6307/07-U-02 (Norwegian Shelf near Trondheim) were analyzed for major and trace elements. These laminated black shales are characterized by high total organic carbon (TOC) and total sulfur (TS) contents as well as by significant enrichments in several redox-sensitive and/or sulfide-forming trace metals (Ag, Bi, Cd, Co, Cr, Cu, Mo, Ni, Re, Sb, Tl, U, V, and Zn). Enrichment factors relative to 'average shale' are comparable to those found in Cenomanian-Turonian boundary event (CTBE) black shales and Mediterranean sapropels. The Re content is high in the studied black shales, with maximum values up to 1221 ng/g. Re/Mo ratios averaging 2.3x10-3 are close to the seawater value. High trace metal enrichments and Re/Mo ratios close to the seawater value point to a dominantly anoxic and sulfidic water column during black shale formation. Interbeds with higher Re/Mo ratios, especially in high-resolution sampled core sections, point to brief periods of suboxic conditions. Additionally, enhanced Zn concentrations in the black shales from the Barents Sea support the assumption that hydrothermal activity was also high during black shale deposition. Trace metal signatures of black shales at different drill sites on a transect along the Norwegian Shelf are not only influenced by water depth but also by their location in the boreal realm. Metal enrichments are higher in the northern compared to the southern sites. Volgian (=Tithonian 151-144 Ma BP) black shales exhibit elevated trace metal contents in comparison to their Berriasian (144-137 Ma BP) counterparts. This probably reflects a change in the circulation pattern during periods of black shale formation. Therefore different paleoceanographic conditions, probably controlled by climatic change linked to the transgression of the paleo-sealevel and the North Atlantic opening, may have developed from the Volgian to the Berriasian.
Keywords: BLACK SHALES; BOREAL REALM; MEDITERRANEAN SAPROPELS; TRACE ELEMENTS; RHENIUM; HIGH RESOLUTION; ANOXIC ENVIRONMENT; Mesozoic::Cretaceous::Upper::Turonian; Мезозой::Меловая::Верхний::Сеноманский; Мезозой::Меловая::Верхний::Туронский; Мезозой::Юрская::Верхний::Титонский; Мезозой::Меловая::Нижний::Берриасский; Mesozoic::Cretaceous::Upper::Cenomanian; Mesozoic::Cretaceous::Lower::Berriasian; Mesozoic::Jurassic::Upper::Tithonian